The Difference in Expression of Autophagy-Related Proteins in Lesional and Perilesional Skin in Adult Patients with Active and Stable Generalized Vitiligo-A Cross-Sectional Pilot Study - Haiyan Yu; Xiaoxia Lin; Yaoyao Huang; Hao Cheng; Oliver Seifert (Wolters Kluwer Medknow Publications, 2021)
Background: Autophagy plays an important role in maintaining intracellular homeostasis and is essential for cell survival and cell death. Dysfunction of autophagy has been described in many autoimmune diseases but data on vitiligo are scarce. Aims: The aim of this pilot study was to investigate the expression of autophagy-related proteins in patients with vitiligo. Methods: Western blotting was used to analyze the expression of microtubule-associated protein light chain 3 (LC3II/I), autophagy-related gene 5 (Agt5), mammalian target of rapamycin (mTOR) and p62 in lesional and perilesional vitiligo skin from seven patients with active generalized vitiligo and nine patients with stable generalized vitiligo compared to control skin from six healthy subjects. Results: Our data showed increased expression of the autophagy marker LC3II/I and decreased p62 protein expression in lesional skin of active and stable vitiligo compared to control skin (P < 0.01). No significant difference in the expression of LC3II/I and p62 was found in perilesional skin of active vitiligo patients (P > 0.05) compared to control skin. Expression of LC3II/I in stable vitiligo lesional skin was higher and p62 expression was lower compared to active vitiligo lesional skin (P < 0.01). Decreased p62 expression was shown in perilesional skin of stable vitiligo patients (P < 0.05). Agt5 protein in lesional and perilesional skin of both active and stable vitiligo patients were increased (P < 0.01 and P< 0.05) compared to control skin. The expression of mTOR protein in lesional and perilesional skin of active and stable vitiligo patients was significantly lower than in control skin (P < 0.01). Conclusions: The present study indicates increased autophagy in lesional skin in vitiligo patients. Stable vitiligo lesional skin showed increased autophagy compared to active vitiligo lesional skin. Missing activation of autophagy in active vitiligo perilesional skin suggests disturbed autophagy to be associated with vitiligo.